PENGUNGKAPAN PERTANGGUNGJAWABAN PEMERINTAH DAERAH DI INDONESIA - Sri Suranta; Sulardi Sulardi; Santoso Tri Hananto; Halim Dedy Perdana (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of the study was to examine the disclosure of accountability of local governments in Indonesia. The problem of this research is whether there are differences in disclosure of accountability between Regional Governments in Java and outside Java Islands. The population of this study is all local governments, both regencies and cities in Indonesia, while the sample is all regencies/cities in Indonesia other than provincial governments. The data of this study are the 2017 Regional Government Financial Statements. Data analysis is to determine the normality of the data using the Kolmogorov-Smirnov test. Hypothesis testing uses the Mann-Whitney test, because the data are not normally distributed. The results of this study are that there are differences in disclosure of accountability between Regional Governments in Java and Outside of Java. Another finding is that the level of disclosure on the island of Java is higher than on the Outside Island of Java.